A STUDY OF THE ROLE OF MNREGA IN ENHANCING SOCIAL HARMONY AND SOCIAL SECURITY IN RURAL SOCIETY - Sharma, Manoj Kumar; Kumar, Yogesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), enacted in 2005, is a key social security initiative by the Government of India that aims to enhance livelihood security in rural areas through the provision of guaranteed wage employment. While the economic implications of MNREGA have been widely studied, this paper explores its broader social dimensions—particularly its role in promoting social harmony and social security within rural society. This study critically examines how MNREGA contributes to reducing social inequalities and tensions by promoting inclusive and equitable access to employment opportunities. By ensuring participation across caste, class and gender lines, MNREGA has been instrumental in challenging traditional social hierarchies, empowering marginalised communities and promoting collective rural development. The research highlights the increased participation of women, Scheduled Castes (SCs) and Scheduled Tribes (STs) in wage employment and how this inclusiveness has enhanced dignity, financial independence and social integration. Additionally, the study examines the role of MNREGA in strengthening social security by providing income support to vulnerable rural households, particularly during lean agricultural seasons or periods of economic distress. This income stability improves access to food, healthcare and education, thereby improving quality of life and reducing social conflict. The research is supported by a review of literature, field data and secondary sources to assess the implementation and outcomes of MNREGA. The findings suggest that despite operational challenges such as delayed payments and bureaucratic inefficiencies, MNREGA continues to serve as an important tool to promote rural equity, economic security and communal cooperation. In conclusion, MNREGA holds significant potential not only as an employment programme but also as a catalyst for social change in rural India. Strengthening its implementation and outreach can further enhance its impact on building a harmonious, secure and inclusive rural society.